Letter (copy) : International Brigade - Tewson, Vincent
034-0128-001 International HVT/WJB/AC/70 30 17th October, 1938. Mr. E. Stephenson, Secretary, Station Engineer Branch No: 5, Electrical Trades Union, 90, Halley Road, FOREST GATE, E.7. Dear Sir, INTERNATIONAL BRIGADE. We have to acknowledge your communication of 15th instant, with regard to the British members of the International Brigade, the contents of which we note. Would you kindly note that resolutions intended for the General Council should come through Head Offices of affiliated Unions. It has been found necessary to adopt this procedure, so as to avoid overlapping, and we should be grateful if you would bear it in mind with respect to any further communication you may wish to make. We thank you for your enquiry about Sir Walter Citrine's health, which is, as far as we know, up to the present, good. Yours faithfully, Assistant Secretary. 292/946/34/128